Job Demand for Professionals Graduated in Cultural Management for Costa Rica, a Quantitative Approach - Alpízar Valverde, Nicolás (2021)
In Costa Rica exists a rich cultural scene, which implies the need for professionals specialized in such a management profile. This paper offers an estimation of the Costa Rican labor demand for professionals in Cultural Management in 2014, as part of a feasibility study to create a specialized career, within the University of Costa Rica. Given the national scarcity of primary data and methodologies for quantification, an own model was proposed, with qualitative support, the scope of which was exploratory and descriptive. To achieve this, relationships were drawn between professional profiles (created by national authors) and organizations that implemented cultural management practices. Using 4 levels of categorization, the ideal number of professionals required was determined, a figure that was weighted by percentages that express the minimum necessary to meet the management needs of each organization. A  athematical model was generated that facilitates the subsequent argumentation. The results are presented using tables and prose. The evaluation is reviewedwith an incremental analysis by scenarios and includes some reflections on the configuration found and the methodological contributions.